Much Ado About Nothing? A Quantitative Analysis of Transatlantic Trade Liberalization - Michael Paul Pflüger; Oliver Krebs (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
This paper explores the quantitative consequences of transatlantic trade liberalization envisioned in a Transatlantic Trade and Investment Partnership (TTIP) between the United States and the European Union. Our key innovation is to base our estimate on a new quantitative trade model with an associated recent technique which is far more parsimonious and has a far tighter connection between theory and data than previous approaches. We make use of the recently established detailed World Input Output Database (WIOD). This allows us to take input-output linkages pertaining among industries into account. We also explore the consequences of labor mobility across the countries of the European Union.
Keywords: F10; F16; F20; 330